IoT Based Smart and Portable System for Remote Patient Monitoring and Drug Delivery. Issue 1 (August 2021) - Kumar, Naveen; Kaushal, Rajesh Kumar; Panda, Surya Narayan
Abstract: In recent, there has been significant development in the healthcare technology particularly due to Internet of Things (IoT). The ubiquitous computing has brought a progressive change in the field of healthcare. In this way, the wellbeing experts are serving the society in a superior manner by utilizing such IoT based gadgets. This paper presents an IoT based model "Smart Portable Intensive Care Unit" for real-time patient monitoring with an additional feature of drug delivery from the remote location. The proposed model assisting the healthcare professionals and the relatives of the patient to monitor the physiological data of the patient from the remote location. The patient's physiological data is transmitted to the cloud. An android based mobile application is developed to fetch the patient's data from the cloud database in real-time. The authenticity of the user is maintained throughout the data communication process. The patient's data is transmitted on the mobile application of the doctor both in analog and digital form. The doctor can also set the flow of drug infusion from a remote location. The proposed model can be effectively used for the patients admitted in the hospital or inside the ambulance.